Lead removal from water by choline chloride based deep eutectic solvents functionalized carbon nanotubes - AlOmar, M.K.; AlSaadi, M.A.; Hayyan, M.; Akib, S.; Ibrahim, R.K.; Hashim, M.A. (Elsevier, 2016)
Deep eutectic solvents (DESs) have gained increasing amounts of interest due to their involvement in variety of applications. In this study, we synthesized six DESs systems based on choline chloride and six different hydrogen bond donors (HBD). Next, the synthesized DESs were used as functionalization agents with carbon nanotubes (CNTs) for use as adsorbents of lead ions, specifically Pb(II), from water. Screening studies for 24 different DES-CNT based adsorbents were conducted. The selected adsorbents samples were characterized using Raman spectroscopy, Fourier transform infrared (FTIR) spectroscopy, XRD, FESEM, EDX, BET surface area, Zeta potential, and thermogravimetric analysis (TGA). Removal percentages and uptake capacities of Pb(II) on the novel selected adsorbents were optimized by RSM-CCD experimental design. The optimum conditions were found to be pH 5 with adsorbent dosage of 5 mg and contact time of 15 min. The maximum adsorption capacity of the selected adsorbent was found to be 288.4 mg/g. Langmuir and Freundlich adsorption isotherm models were also investigated and three kinetic models of adsorption were studied.